YTO : a pioneer in China's express business model - McFarlan, F. Warren (Franklin Warren); Li, Donghong; Cao, Shanshan (London : Tsinghua University School of Economics and Management, 2015)
One day in May 2015, Yu Weijiao, Chairman of Shanghai YTO Express (Logistics) Co., Ltd. was preparing a video lecture for the 15th anniversary of YTO a few days later. His heart was as bright as the sunlight. The video camera reminded him of his first speech ten years ago. In December 2005 when he was invited to the first China Express Industry Development Summit, he was so nervous that he almost forgot what he had said except for the closing words: "Both direct operation and franchise system in the express industry operation with Chinese socialist characteristics will coexist forever." The words generated a great sensation among the audience as the blending mode was not yet approved by the Chinese regulatory agencies. However, thanks to its specific business mode combining direct operation with franchise operation, YTO had become a pioneer in China's private express industry, and was developing at a much faster pace.
Originally published in McFarlan, F. W., Li, D., & Cao, S. (2015). YTO: A pioneer in China's express business model. 0-715-331. Beijing: Tsinghua SEM Chinese Business Case Center.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Weijiao, Yu; YTO Express (Logistics) Co., Ltd; China Express Industry Development Summit; Business enterprises